2022
DOI: 10.20343/teachlearninqu.10.13
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Accessibility to Academic Support in Higher Education for Diverse Student Cohorts

Abstract: Academic support at Australian universities has become an important aspect of higher education, as student cohorts continue to diversify, and universities need to ensure the students’ success and the institutions’ reputations. Often, students in need do not access academic support services and little is known about what influences students’ decisions to seek academic support. This small-scale qualitative study aims to clarify why students (do not) engage in support and what could be changed to make services mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The concept of institutional problem normalization, as presented in this paper, is rather novel; however, in their study, Bornschlegl and Caltabiano (2022) found reducing public stigma around academic help-seeking behaviors led to greater use of resources. Additionally, Hammond et al (2015) advocated for institutions to normalize help-seeking behaviors in the academic setting so students might use academic resources more frequently.…”
Section: Problem Normalizationmentioning
confidence: 85%
See 2 more Smart Citations
“…The concept of institutional problem normalization, as presented in this paper, is rather novel; however, in their study, Bornschlegl and Caltabiano (2022) found reducing public stigma around academic help-seeking behaviors led to greater use of resources. Additionally, Hammond et al (2015) advocated for institutions to normalize help-seeking behaviors in the academic setting so students might use academic resources more frequently.…”
Section: Problem Normalizationmentioning
confidence: 85%
“…Many students do not seek help because they associate help-seeking with feelings of inadequacy and inferiority (Winograd & Rust, 2014). Further, there is a stigma around seeking help and using academic support services, meaning that students may feel judged for needing such support (Bornschlegl & Caltabiano, 2022). The developmental concepts that help explain a lack of help-seeking behavior include (a) involvement or time spent doing educational activities (Astin, 1984); (b) engagement or purposeful student-faculty contact and active and collaborative learning (Kuh, 2001); and (c) integration or how much a student comes to share the attitudes and beliefs of their peers and faculty and how closely they follow the rules of the institution (Tinto, 1975;Tinto, 1993).…”
Section: Stigma Around Academic Help-seeking Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about what influences students' decisions to seek academic support and what could be changed to make services more accessible and engaging. In a recent study (Bornschlegl & Caltabiano, 2022) found that the promotion of services needs to be improved and stigma about seeking academic support should be addressed. For example, to normalize accessing academic support, student success centers can be particularly effective when they are perceived as a service that everyone uses -not just those who are struggling academically.…”
Section: Discussionmentioning
confidence: 99%
“…Using drawings to Understand Students’ Help-Seeking Behavior To explore undergraduate students’ help-seeking behavior about writing papers that require research 220 undergraduate students Quantitative Results indicated that students usually receive help from peers and family members after drafting papers. Research-related tasks are the most challenging, but librarians are rarely sought for help 37 7 Bizuneh [ 91 ] (2022) Ethiopia Belief in counseling service effectiveness and academic self-concept as correlates of academic help-seeking behavior among college students To examine the association between homework practices of college students, motivation, self-regulation of learning, and final course grades 133 college students drawn from a small private college in urban New York Quantitative Results indicated that using homework logs and considering self-efficacy, motivation, and help-seeking strategies related to homework completion can promote self-directed learning 30 8 Bornschlegl [ 92 ] (2021) Australia Application of the theory of Planned Behavior to identify variables related to academic help seeking in higher education To identify personality variables, background variables, and variables related to the Theory of Planned Behavior that can predict academic help-seeking in higher education to inform the design of engaging and accessible academic support 430 students participated in the survey Quantitative The study found that only a small portion of the variance of academic help-seeking behavior could be explained, indicating the need for interventions to increase help-seeking 39 9 Bornschlegl [ 93 ] (2022) Australia Increasing accessibility to academic support in higher education for diverse student cohorts To clarify why students (do not) engage in support and what could be changed to make services more accessible and engaging ...…”
Section: Table A1mentioning
confidence: 99%